Sustainable Regional Planning - Almusaed, Amjad; Almssad, Asaad (IntechOpen, 2023)
Sustainable development involves balancing economic growth with current and future needs. Regional sustainable development faces many challenges. Sustainability requires zone-specific indicators. Regional planning is essential for sustainable development because land use, transportation, and energy are interdependent. Europe, especially Scandinavia, could lead sustainable practices due to its progressive government and infrastructure. Data-driven, global efforts are needed for sustainable development. Regional projects test new ideas. Sustainable regional planning requires integrated decision-making, social equity, natural resource protection, and community resilience. It balances economic growth and environmental protection. This book provides a comprehensive overview of sustainable regional planning. It emphasizes sustainability in regional planning and the roles of various actors in promoting sustainable development. Global urbanization requires sustainable urban and regional planning. This book's framework integrates environmental and economic goals, benefiting students and professionals. It reconciles private property rights and public interest in protecting natural and cultural resources in suburban, urban planning. The book includes three sections on "Principles of Sustainable Urban Planning", "Case Studies", and "Challenges and Future Directions". It presents a comprehensive and informed perspective on sustainable regional planning in urban areas. It offers a detailed examination and evaluation of diverse concepts and approaches to contemporary sustainable regional planning and their implications for human livelihoods. Finally, the book explores the relevance of sustainability in modern society, shedding light on the multiple dimensions of this topic and their influence on human well-being.